2006
DOI: 10.1143/jjap.45.4296
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Trace Phenol in Solution Using Gas–Liquid Interface Discharge

Abstract: Many researchers have investigated the decomposition of trace phenol in solution using liquid-phase discharge. However, liquid-phase discharge has a problem of consuming an extremely high energy. We have investigated phenol decomposition using a gas–liquid interface discharge induced by an ultra-short width (∼600 ns) pulse of high voltage. Gas bubbling was employed to enhance both convection and the gas–liquid interface area, because chemical reactions take place mainly at the surface of a solution. A signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…And these active gas species react with water to produce OH radical, singlet oxygen and other active species. Among these species, it is thought that the OH radical has the potential to oxidize organics to carbon dioxide and water (Kuroki et al, 2006). Therefore, oxygen and nitrogen plasma were selected as high OH radical production plasma gas species , and TTX solution were treated.…”
Section: Resultsmentioning
confidence: 99%
“…And these active gas species react with water to produce OH radical, singlet oxygen and other active species. Among these species, it is thought that the OH radical has the potential to oxidize organics to carbon dioxide and water (Kuroki et al, 2006). Therefore, oxygen and nitrogen plasma were selected as high OH radical production plasma gas species , and TTX solution were treated.…”
Section: Resultsmentioning
confidence: 99%
“…Electrons ( 3 were generated in air by atmospheric discharge [15]. Miyazaki et al found, using a gas detector, that O 3 , NO, and NO 2 were generated in a N 2 -O 2 gas mixture upon pulse discharge [4].…”
Section: IIImentioning
confidence: 99%
“…For example, researchers have reported the decomposition of phenol [1][2][3], organic dyes [4,5], and acetic acid (as a model of persistent organic substances) [6] in water using on-water pulse discharge and the decomposition of organic dyes [7,8] in water using on-water atmospheric-pressure plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is ongoing on water purification by the decomposition of harmful organic compounds in water using discharges and plasmas, such as underwater pulsed streamer corona discharge [1,2], underwater RF plasma within bubbles [3,4], atmospheric-pressure pulse discharges on water [5,6], and atmospheric-pressure plasma on water [7,8]. Previously, we directly irradiated a plasma jet, which can be released into the atmosphere using our device [9], onto an aqueous solution containing methylene blue, a blue dye used as a model organic substance, and reported the resulting decolorization of the methylene blue aqueous solution [10].…”
Section: Introductionmentioning
confidence: 99%